1.3k views
0 votes
Write the standard equation of the circle below.

(x + 1)2 + (y - 2)^2 = 1

(x - 1)2 + (y - 2)^2 = 1

(x + 1)2 + (y + 2)^2 = 1

(x - 1)2 + (y - 2)^2 = 1

Write the standard equation of the circle below. (x + 1)2 + (y - 2)^2 = 1 (x - 1)2 + (y-example-1
User Sarper
by
5.3k points

2 Answers

3 votes

Answer:

Choice 1 is correct answer.

Explanation:

Since , we know that

(x-a)²+(y-b)² = r² is equation of circle Where r is radius of circle and (a,b) is center of circle.

From diagram , we notice that

center of circle is (a,b) = (-1,2)

Radius is 1.

a = -1 and b =2 and r = 1

Putting above values in equation of circle, we have

(x-(-1))²+(y-(2))² = (1)²

simplifying

(x+1)²+(y-2)² = 1 which is the answer.

User Jayflo
by
5.2k points
5 votes

Answer:


(x+1)^(2) +(y-2)^(2) =1

Explanation:

we know that

the equation of the circle into center radius form is equal to


(x-h)^(2) +(y-k)^(2) =r^(2)

where

r is the radius of the circle

(h,k) is the center of the circle

In this problem we have


(h,k)=(-1,2)


r=1\ units

substitute


(x+1)^(2) +(y-2)^(2) =1^(2)


(x+1)^(2) +(y-2)^(2) =1

User Weltraumpirat
by
5.3k points